1975
DOI: 10.1093/clinchem/21.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanized Enzymatic Determination of Triglycerides in Serum

Abstract: A procedure for enzymatic determination of serum triglycerides [Clin. Chem. 19, 476 (1973)] has been adapted for use in continuous-flow analysis (Technicon AutoAnalyzer). A very simple manifold is used; serum is incubated at 37 °C with the lipase and α-chymotrypsin in potassium phosphate buffer (0.1 mol/liter, pH 7, containing 1.50 g of bovine serum albumin per liter). The liberated glycerol is dialyzed against the complete glycerol reagent. The change in absorbance at 340 nm resulting from oxidation of NADH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…High‐density lipoprotein (HDL) levels were measured according to the method described by Finley (1978). Trigyceride levels were measured using Stanbio Liquicolor Triglyceride kit according to the method described by Bucolo et al. (1975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High‐density lipoprotein (HDL) levels were measured according to the method described by Finley (1978). Trigyceride levels were measured using Stanbio Liquicolor Triglyceride kit according to the method described by Bucolo et al. (1975).…”
Section: Methodsmentioning
confidence: 99%
“…High-density lipoprotein (HDL) levels were measured according to the method described by Finley (1978). Trigyceride levels were measured using Stanbio Liquicolor Triglyceride kit according to the method described by Bucolo et al (1975). LDL level was measured by subtracting both levels of HDL and one-fifth of triglycerides from the levels of total cholesterol (Friedewald et al 1972).…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…4 The optimal pH for GDH is 10.0, while the Km values for glycerol and NAD + are 1.10 and 0.089 mmol/L, respectively, and the reaction is reversible. 6 For this reason, a simple endpoint assay for TGs using GDH is not a practical strategy. Many research groups have reported assaying TGs using GDH until now.…”
Section: Discussionmentioning
confidence: 99%
“…In these methods, TGs were hydrolysed by lipoprotein lipase (LPL, EC 3.1.3.34) to glycerol and fatty acids, and the substances subsequently derived from glycerol were modified by various dyes and assayed by colorimetric methods (enzymatic colorimetric method). 6,7 Moreover, with the progression of scientific technologies, other assay methods have been reported, including those using chromatography, nuclear magnetic resonance, mass spectrometry and bio-sensors. 811 All these methods have a high accuracy and sensitivity; however, because special instruments and trained personnel are required for their execution, the introduction of these methods into the clinical setting has not been smooth.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid testing was performed at the Heinz Nutrition Laboratory at the University of Pittsburgh. [28][29][30] We started by categorizing each man as either receiving or not receiving statin therapy. This was determined by participant self-report at Visit 56.…”
Section: Discussionmentioning
confidence: 99%